El pensamiento de Kant en algunas teorías recientes de justicia social - Bertomeu, María Julia (2000)
ln this paper, the author examines the possibility of our having a theory of social social justice which is compatible with the Kantian system as a whole. She discusses several competing views and puts forward her own proposal about the problem.